Semelhanças e diferenças de habilidades sociais entre crianças com síndrome de Down incluídas e crianças com desenvolvimento típico - Pereira, Mariana Sarro (Universidade Federal de São Carlos, 2007)
Recent works about students inclusion have shown that it brings significant improvement to the social and cognitive development to the major part of students with special educational needs, included those with Down syndrome. Considering the benefits of that inclusion, and this process based on social interaction, it can be supposed that the social relationships are significant to the social and cognitive development for children in the general, as well as for those with special educational needs. The results of researches concerning to social skills of children with Down syndrome are controversial: some of them point out that these individuals are highly sociable while others state difficulties in their social behavior. Considering this imbalance, the present work had as objectives: 1) identify the social skills repertoire from both groups of students, with Down syndrome and with typical development; 2) compare similarities and differences of the social skills repertoire between the groups; 3) verify the correlation among the frequency, the adequation and the difficulty to emit social skills reactions trough the self-evaluation; 4) verify the correlation between selfevaluation and the evaluation done by teachers about social skills reactions; and 5) verify the differences of social skills intrinsic of each group as a function of their own characteristics. In this research were included 10 children with Down syndrome, 10 children with typical development and their teachers. The scores to evaluate the social skills were obtained through IMHSC-Del-Prette (Inventário Multimídia de Habilidades Sociais de Crianças-Del-Prette) tool. T-test and Pearson Correlation Coefficient performed statistical analyses. The results allowed verify similarities between the groups as far as passive behavior was concerned. Related to active and skilled behavior it had been found differences between groups. Generally, children with Down syndrome showed some deficits in their social skills repertoire in comparison with children with typical development. Also had been verified a positive correlation between scores of social skills self-evaluation, as well as between scores of social skills self-evaluation and these done by teachers. In the intrinsic social skills differences of each group, the Down syndrome children were affected by type of school and learning disabilities, while typical development children were affected by gender and learning disabilities. In spite of the natural characteristics of the syndrome, it is necessary to look with special attention to the characteristics learned by these individuals. The adequate stimulation of their environments it is of fundamental importance for their development and learning
Keywords: Estudantes com necessidades educacionais especiais; Habilidades sociais; Inclusão escolar; Down, Síndrome de; School inclusion; Down syndrome; Social skills; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL